ISLAM DAN NEGARA - Yayu Andika Amin; Istiqama; Abbas; Dahlan Lama Bawa (STKIP Subang, 2026)
Islam is a religion that regulates all aspects of human life, both spiritually and socially, including national and state life. The relationship between Islam and the state is an important study because Islam not only regulates the relationship between humans and Allah SWT, but also organizes social, political, and governmental life to achieve justice and the welfare of the people. This study aims to examine the meaning of Islam, the concept of the state, and Islamic views on the state from the perspectives of classical and contemporary scholars. The research method used is a qualitative approach with a library research type. Data were obtained through a review of primary sources such as the Qur'an and the works of scholars, as well as secondary sources in the form of books and relevant scientific literature. Data were analyzed using descriptive-analytical methods to gain a comprehensive understanding of the concepts of Islam and the state. The results of the study indicate that in the Islamic perspective, the state is a means to uphold justice, safeguard the public interest, and regulate community life based on divine and humanitarian values. Islam does not separate religion and the state, but rather views the two as a complementary entity. Basic principles such as monotheism, justice, deliberation, equality, and the welfare of the people are the main foundations of state governance according to Islam. Therefore, from an Islamic perspective, the state functions as a tool for realizing a just, moral, and divinely-based social order.